Publication trends and the network of publishing institutions in accounting: data on The Accounting Review, 1926–2014. (2nd January 2017) - Lohmann, Christian; Eulerich, Marc
ABSTRACT: Our study charts the development of the accounting community by tracing publication trends and changes in methodology, including a major shift towards positive and neoclassical economics, multi-authorship and the prevalence of particular institutions, as reflected in The Accounting Review ( TAR ) between 1926 and 2014. Using network analysis, we identify distinct networks in this community and show that while the network of the institutions to which TAR authors were affiliated in the analysed period became diverse, the network of the institutions from which TAR authors received their doctorate remained dominated by a relatively small group of élite US universities.